teorema double butterfly - Nur Azira (Jurnal Pustaka Cendekia Pendidikan, 2024)
The butterfly theorema was first introduced by W.G Homer in 1815 in a gentlemen’s diary. Many mathematicians make developments and variations of these theorems, for example the butterfly on circle theorema. In 1976 a mathematician named Dixon Jones made a variation on the development of the butterfly theorema on circles which was then called the double butterfly theorema on circles. In 1990 the double butterfly theorema was again discussed by a mathematician named Larry Hoehn. This theorema is called the duble butterfly theorem because the contents of this theorema, when described, form four triangles that resemble two pairs of butterfly wings.